PENGARUH PENANAMAN MODAL ASING, PENANAMAN MODAL DALAM NEGERI, DAN PENDAPATAN ASLI DAERAH TERHADAP PERTUMBUHAN EKONOMI - Ratna Sari Dewi; Sriwardani Sriwardani (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2017)
This research is to find out and analysis the influence of PMA, PMDN, and PAD and the significant to the economic growth in Indonesia. The population are 34 province since 2013-2015. Samples that is chosen with purposive method and using SPSS as the tools. The results show that PMA, PMDN and PAD have positive influence with significant both partial or simultaneous.Keywords: PMA, PMDN, PAD and economic growth